Pengaruh Kompetensi Sumber Daya Manusia dan Budaya Organisasi terhadap Kinerja Badan Perencanaan Pembangunan Daerah Kabupaten Batang - Drina S, Ria Mustikah; Sulandari, Susi; Rihandoyo, Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
In every organization needs qualified elements to maximize its performance. The resources in question can be physical such as human resources or non physical such as regulation, information and policies. The role of resources in the organization is very important because with the resources here's what became a driving factor for the Organization to achieve the objectives that have been set. Organizational performance is not optimal is that underlying this research, where he did not achieve value for money in the implementation of the programme of work/activities implemented and still less sesuainya a knowledge of human resources assigned to the field. Therefore need to saw the driving factors that can affect the performance of an organization. These studies use quantitative analysis approach. The sample used in this study as many as 35 respondents who were employees of the regional development planning board in Batang district. Analysis of the correlation test and konkordasi kendall was used in this research. From the results of this study demonstrate the performance of the regional development planning board in Batang district belongs to high of category with 77.1%. The magnitude of the influence of Competence (X1) against the performance of the Organization (Y) is equal to 14.8% whereas the influence of organizational culture (X2) against the performance of the Organization (Y) is equal to 15.4%. Then between Competence (X1) and organizational culture (X2) affects organizational performance (Y) simultaneously by 2.25%. Results of this study showed a significant coherence between the competence of human resources and organizational culture to organizational performance.